An Unusual Case of Mitral Stenosis with Coronary Ar- tery and Left Ventricular Apical Aneurysm - Mohammad Masoumi; Maryam Aliramezany (Journal of Tehran University Heart Center, 2015)
The left ventricular aneurysm is one of the most significant complications of myocardial infarction and is defined as the expansion of the ventricular wall. The coronary artery aneurysm is characterized by an abnormal dilation of the localized portion of the coronary artery, and its main cause is atherosclerosis. We herein report an unusual case of coronary artery and left ventricular aneurysms in a mitral stenosis patient with normal coronary arteries and no sign of atherosclerosis. This patient was a known case of mitral stenosis due to rheumatic heart disease and was symptomatic despite optimal medical therapy. Laboratory tests were normal, and electrocardiography showed sinus rhythm and left atrium abnormality without pathologic Q wave. Angiographic view illustrated left circumflex artery and left ventricular apical aneurysms. Percutaneous transvenous mitral commissurotomy was performed successfully and the patient was discharged with Warfarin and a beta blocker. No symptom was observed at six months' follow-up.